Dilema Apresiasi Guru: Antara Hak atas Penghargaan dan Tuduhan - Eni Setiawati; Nasywa Intan Azzahra; Serly Oktavianti; Suhertina Suhertina (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The phenomenon of giving gifts to teachers often causes a dilemma between good intentions and gratification that can lead to legal problems. This study aims to analyze the ethical and legal boundaries in giving gifts to teachers and their impact on the protection of the teaching profession. The method applied in this study is descriptive qualitative with a literature approach. Data were collected from various legal sources, regulations, and other academic references. The findings of the study revealed that the main difference between gifts and gratification lies in the intention and situation when giving. Gifts given sincerely without any expectation of return should not be a problem, while gratification that has elements to influence the teacher's decision can be considered a violation of the law. Clear policies and public education are needed so that awards to teachers are not misinterpreted as a legal act that violates the law.